Evolution of the selfing syndrome: Anther orientation and herkogamy together determine reproductive assurance in a self‐compatible plant. (1st September 2017) - Toräng, Per; Vikström, Linus; Wunder, Jörg; Wötzel, Stefan; Coupland, George; Ågren, Jon
Abstract: Capacity for autonomous self‐fertilization provides reproductive assurance, has evolved repeatedly in the plant kingdom, and typically involves several changes in flower morphology and development (the selfing syndrome). Yet, the relative importance of different traits and trait combinations for efficient selfing and reproductive success in pollinator‐poor environments is poorly known. In a series of experiments, we tested the importance of anther–stigma distance and the less studied trait anther orientation for efficiency of selfing in the perennial herb Arabis alpina . Variation in flower morphology among eight self‐compatible European populations was correlated with efficiency of self‐pollination and with pollen limitation in a common‐garden experiment. To examine whether anther–stigma distance and anther orientation are subject to directional and/or correlational selection, and whether this is because these traits affect pollination success, we planted a segregating F2 population at two native field sites. Selection strongly favored a combination of introrse anthers and reduced anther–stigma distance at a site where pollinator activity was low, and supplemental hand‐pollination demonstrated that this was largely because of their effect on securing self‐pollination. The results suggest that concurrent shifts in more than one trait can be crucial for the evolution of efficient self‐pollination and reproductive assurance in pollinator‐poor habitats.